Compliance Through Persuasion Not Force - Kashyap, Sonakshi (Trinity Law Review, 2021)
Our constitution guarantees to all citizens of India, the right to freely conduct any trade or commerce. To realize this fundamental right, the state is required to ensure free markets that run on principles of fair competition. The Competition Act, 2002 deals with the regulation of competition in Indian markets, and the Competition Commission of India (CCI) is the nodal agency which undertakes the enforcement of this Act. One of the thrust areas of the Competition Act is ‘Competition Advocacy’, which aims at building a competition friendly environment by creating awareness about the importance of fair competition amongst the different stakeholders in a market place. Competition advocacy, therefore, helps in creation of healthy markets, aware consumers, ready compliance with competition law, and thereby reduces the burden of CCI. Competition advocacy in foreign jurisdictions is usually carried out by autonomous bodies through their involvement in early stages of policy making and assessment of their potential impact on competition. The Indian law provides that it is the duty of CCI to promote competition advocacy, and give its opinion on policy matters affecting competition if the same is requested by governments at Central or State levels. The CCI has undertaken various initiatives, like, research programmes, collaboration with different institutions, etc. to effectively create awareness around fair business practices. However, the Indian law is insufficient to adequately achieve the goal of competition advocacy. The law, therefore, needs to be amended by giving more power to CCI. CCI should be allowed to offer suo-moto opinions on policies that in its belief affect competition, further such opinion should be given due significance and not rejected without legitimate grounds being recorded for the same. Competition advocacy, can also be improved by ensuring autonomy and transparency in functioning of CCI, use of social media in creating public awareness, carrying out Regulatory Impact Assessment (RIA) of policies etc.